Fisherwomen’s Participation in Fisheries: A Case Study of Bargi Reservoir in Madhya Pradesh, India - Katre, Nidhi; Ojha, Shekhar Nath; Sharma, Arpita (Fishery Technology, 2023)
A study was conducted in Bargi reservoir in Madhya Pradesh state, India with the objectives of exploring membership and participation of men and women in Fisheries Cooperative Societies (FCS) and constraints perceived by them. The study revealed that only 8.88 % fisherwomen had membership in the FCS even when 80.54 % of them were engaged in fisheries activities. Involvement of fisherwomen was in fish smoking (33.33 %), fish trading (12.22 %), fish harvesting (11.11 %) and net making/repairing (23.88 %). Fisherwomen were engaged for 8 hours/day in productive work and 9 hours/day in reproductive and community work. Poor social status, poor social acceptance and lack of ownership of assets were major social constraints. In addition, less income, lack of working capital and lack of alternative livelihood opportunities during closed fishing season were also reported. Gender bias in getting membership in FCSs, limited access to training and extension services and lack of access to financial saving schemes were the main institutional constraints.